2008
DOI: 10.1161/circulationaha.107.730101
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Receptor Blockade Reduces Tachycardia-Induced Atrial Adhesion Molecule Expression

Abstract: Background-Increased levels of inflammatory markers are predictors of thromboembolic events during atrial fibrillation (AF).Increased endocardial expression of adhesion molecules (ie, vascular cell adhesion molecule [VCAM] and intercellular adhesion molecule [ICAM]) could be an important link between initiation of inflammatory and prothrombogenic mechanisms responsible for thrombus development at the atrial endocardium (endocardial remodeling). Methods and Results-Tissue microarrays were used to screen right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 43 publications
(40 reference statements)
7
96
1
4
Order By: Relevance
“…In our analysis, after 6 months following ACS and optimal medical therapy, sVCAM-1 concentration increased (p = 0.01). There are studies heralding the role of VCAM-1 in the optimization of CAD therapy, as it was shown that a decrease in the expression of VCAM-1 can be observed along with the administration of antioxidants and polyunsaturated fatty acids as well as in patients chronically treated with ACE inhibitors, statins and fibrates [13][14][15][16]. The elevation of sVCAM-1 seen in our study following the six-month-long optimal medical therapy might require further explanation.…”
Section: Discussionmentioning
confidence: 59%
“…In our analysis, after 6 months following ACS and optimal medical therapy, sVCAM-1 concentration increased (p = 0.01). There are studies heralding the role of VCAM-1 in the optimization of CAD therapy, as it was shown that a decrease in the expression of VCAM-1 can be observed along with the administration of antioxidants and polyunsaturated fatty acids as well as in patients chronically treated with ACE inhibitors, statins and fibrates [13][14][15][16]. The elevation of sVCAM-1 seen in our study following the six-month-long optimal medical therapy might require further explanation.…”
Section: Discussionmentioning
confidence: 59%
“…305 Endocardial thrombogenic alterations in diseased atria, which appear to be related to oxidative stress, appear to contribute to clot formation, particularly in the left atrial appendage. [306][307][308][309][310] Thus, the impact and the relation between EHRAS Classses and the extend of endocardial thrombogenic alterations have to be assessed in future studies. Interestingly, duration of AF does not correlate with the extent of abserved endocardial changes.…”
Section: Prothrombotic Indices: Coagulation Plateletsmentioning
confidence: 99%
“…Soluble VCAM-1 levels appear to be an independent predictor of atrial thrombi in multivariate analysis of variance. 6,15,18,23,24 Recently, in ex vivo experiments using organotypic human atrial tissue cultures and in vivo experiments, we found increased atrial expression of VCAM-1 in patients with paroxysmal and persistent atrial fibrillation. Importantly, it was shown that increased expression of atrial adhesion molecules and reduced levels of nitric oxide occur within hours of rapid atrial pacing and is related to increased oxidative stress and generation of reactive oxygen species.…”
Section: Dovepressmentioning
confidence: 98%
“…6,7,14,15 The remodeling processes mentioned earlier affect myocardial cells and the atrial endothelium ("endocardial remodeling"). Endothelial damage and prothrombotic endothelial alteration are present in fibrillating atria.…”
Section: Prothrombotic Endocardial Remodelingmentioning
confidence: 99%
See 1 more Smart Citation